Frequency and immunophenotype of IL10‐producing regulatory B cells in optic neuritis. Issue 3 (27th December 2018) - Lundqvist, Sara; Modvig, Signe; Fischer, Emilie A.; Frederiksen, Jette L.; Degn, Matilda
Summary: Mouse models of multiple sclerosis (MS) have shown the importance of interleukin‐10 (IL‐10) ‐producing regulatory B (Breg) cells in dampening disease activity and inhibiting disease initiation and progression. In MS and other autoimmune diseases decreased frequency and functionality of Breg cells correlate with disease activity and the percentage of IL‐10‐producing Breg cells decreases during relapse and normalizes in remission. Optic neuritis (ON) is a common first clinical manifestation of MS and IL‐10‐producing Breg cells may be crucial in the transition from ON to MS, we therefore investigate the frequency and function of Breg cells in ON as a clinical model of early demyelinating disease. B cells were purified from 27 patients with ON sampled close to symptom onset (median 23 days, range 7–41 days) and 13 healthy controls. The B cells were stimulated and cultured for 48 hr with CD40 ligand and CpG before measurement of intracellular IL‐10 and the surface markers CD19, CD1d, CD5, CD24, CD38 and CD27 by flow cytometry. The frequency of B‐cell subsets was analysed in peripheral blood and cerebral spinal fluid (CSF) of patients. Sixty‐five per cent of the IL‐10‐producing Breg cells co‐expressed CD24 and CD38, and only 14% were CD24 high CD27 +, suggesting that the naive B cells are the primary source of IL‐10 in the B‐cell culture, followed by memory cells in both healthy controls and patients. The frequency of naive CD19 + CD24 + CD38 + Breg cells was higher in patients with ON compared with controls. The ability of Breg cells to produce IL‐10 was at normal levels in both ON patients with high risk and those with low risk of progression to MS. We found no correlation between Breg cell function and the presence of brain white matter lesions by magnetic resonance imaging or CSF oligoclonal bands indicative of ON patients carrying a higher risk of conversion to MS. The frequencies of IL‐10‐producing B cells did not correlate with the conversion to MS at 2‐year follow up. Interleukin‐10 was primarily produced by naive and memory B cells. The frequency of IL‐10‐secreting B cells did not correlate with risk factors of MS. Breg cell function at clinical onset of ON is not a determining factor for conversion to MS. Abstract : Interleukin 10 (IL‐10) prodicing regulatory B cells have been found to ameliorate the disease progression in animal models of multiple sclerosis. We investigated the frequency of regulatory B cells in healthy controls and in patients with optic neuritis, which is a common first manifestation in multiple sclerosis. There were no differences in the IL‐10 production by B cells in healthy controls and optic neuritis patients with a high risk of progressing to multiple sclerosis.